2002
DOI: 10.1089/109629602760105781
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor Binding Protein-3 Is Upregulated in LPS-treated THP-1 Cells

Abstract: THP-1 cell apoptosis is increased in response to LPS stimulation and is associated with a significant induction of IGFBP-3 mRNA and protein. IGFBP-3, which reportedly promotes apoptosis and modulates the bioavailability of the pro-survival insulin-like growth factor 1, may serve to regulate apoptosis in monocytic cells in an IGF-independent manner. These data further support the investigation of the role of the IGF axis in programmed cell death of immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…On the other hand, we detected an increase in IGFBP-3 mRNA expression in peripheral monocytes after VLCD reaching even higher levels than in control group. This finding could be important since IGFBP-3 was reported to be involved in the induction of growth arrest and apoptosis and to exert antiproliferative activity against myeloid leukemia cells (Ikezoe et al, 2004) and to be induced by LPS (lipopolysaccharide) stimulated apoptosis of human monocytic cells (Agnese et al, 2002). We therefore suggest that the increase of IGFBP-3 expression in peripheral monocytes after VLCD found in our study could have contributed to the downregulation of proinflammatory monocytic activity associated with VLCD-induced metabolic improvement.…”
supporting
confidence: 57%
“…On the other hand, we detected an increase in IGFBP-3 mRNA expression in peripheral monocytes after VLCD reaching even higher levels than in control group. This finding could be important since IGFBP-3 was reported to be involved in the induction of growth arrest and apoptosis and to exert antiproliferative activity against myeloid leukemia cells (Ikezoe et al, 2004) and to be induced by LPS (lipopolysaccharide) stimulated apoptosis of human monocytic cells (Agnese et al, 2002). We therefore suggest that the increase of IGFBP-3 expression in peripheral monocytes after VLCD found in our study could have contributed to the downregulation of proinflammatory monocytic activity associated with VLCD-induced metabolic improvement.…”
supporting
confidence: 57%
“…It has been reported that IL6, IL1b and TNF increase the biosynthesis of IGFBP3 in primary cocultures of hepatocytes and Kupffer cells, whereas the biosynthesis of IGF1 is inhibited (Lelbach et al 2001). The stimulatory in vitro effect of cytokines on Igfbp3 has been described in other cell types such as salivary gland tumour (Katz et al 1999) and human monocytic cell line GLI1 (Agnese et al 2002). Similar to our data, no effect of LPS on Igfbp3 has been observed in primary rata microglia cultures, whereas LPS decreased Igfbp5 and -6 (Chesik et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, several studies have demonstrated the impact of different IGFBPs on monocyte/macrophage. An increase of IGFBP3 expression was first reported to be related with increased monocyte apoptosis stimulated by lipopolysaccharide, which was proved to be IGF independent (99). Recently, IGFBP3 was demonstrated to inhibit monocyte-endothelial cell adhesion through down-regulate ICAM-1 expression under hyperglycemic condition, which can inhibit retinal inflammation (100).…”
Section: Igfbps In Autoimmune Diseases: Possible Mechanismsmentioning
confidence: 99%